The Expression of AQP1 IS Modified in Lung of Patients With Idiopathic Pulmonary Fibrosis: Addressing a Possible New Target - Galán-Cobo, Ana; Arellano-Orden, Elena; Sánchez Silva, Rocío; López-Campos, José Luis; Gutiérrez Rivera, César; Gómez Izquierdo, Lourdes; Suárez-Luna, Nela; Molina-Molina, María; Rodríguez Portal, José A.; Echevarría, Miriam (Frontiers in Molecular Biosciences, 2018)
Activation of the epithelial-mesenchymal transition process (EMT) by which alveolar cells in human lung tissue undergo differentiation giving rise to a mesenchymal phenotype (fibroblast/miofibroblasts) has been well recognized as a key element in the origin of idiopathic pulmonary fibrosis (IPF). Here we analyzed expression of AQP1 in lung biopsies of patients diagnosed with IPF, and compared it to biopsies derived from patients with diverse lung pneumonies, such as hypersensitivity pneumonitis, sarcoidosis or normal lungs. Immunostaining for AQP1 showed a clear increment of AQP1 localized in the alveolar epithelium in biopsies from IPF patients alone. Moreover, to examine the possible participation of AQP1 in the pathophysiology of IPF, we evaluated its role in the pro-fibrotic transformation induced by transforming growth factor (TGF-β) in vitro. Human alveolar epithelial cells (A549), and fibroblasts derived from an IPF patient (LL29), or fibroblasts from healthy normal lung tissue (MRC-5), were treated with TGF-β, and levels of expression of AQP1, as well as those of E-cadherin, vimentin, α-SMA and collagen were analyzed by RT-qPCR, western blot and immunohistochemistry. An increase of AQP1 mRNA and protein after TGF-β treatment (4 to 72h) was observed either in A549 or IPF fibroblast-LL29 but not in MRC-5 fibroblasts. A gradual reduction of E-cadherin, and increased expression of vimentin, with no changes in α-SMA levels were observed in A549. Whereas in LL29 and MRC-5, TGF-β1 elicited a large production of collagen and α-SMA that was significantly greater in IPF fibroblast-LL29. Changes observed are consistent with activation of EMT by TGF-β, but whether modifications in AQP1 expression are responsible or independent events occurring at the same time is still unknown. Our results suggest that AQP1 plays a role in the pro-fibrotic TGF-β action and contributes to the etiology and pathophysiology of IPF. Understanding AQP1’s role will help us comprehend the fate of this disease.